2022
DOI: 10.17650/2313-805x-2022-9-2-32-42
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of circulating in blood tumor DNA as a marker of minimal residual disease in stage I–III colorectal cancer

Abstract: Introduction. Studies on non-metastatic colorectal cancer have demonstrated the prognostic role of circulating tumor (ctDNA) after surgery, and the ability to identify patients with the greatest risk of progression. This makes it possible in the future to personalize neoadjuvant and adjuvant treatment.The study objective – to evaluate the correlation of the ctDNA status before and after surgery with a clinical outcome in patients with stage I–III colorectal cancer.Materials and methods. The study included data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The subgroup analysis demonstrated that in addition to the ctDNA status, its dynamics should be considered, as the conversion of ctDNA from positive to negative from 4 to 12 wk after surgery might determine a more favorable prognosis (HR = 52.3, 95%CI: 7.2-380.5; P < 0.001)[ 37 ]. Polyanskaya et al [ 38 ] also confirmed the prognostic significance of ctDNA positivity after surgery in patients with stages I-III CRC. The 1-year PFS in the groups of positive and negative ctDNA status was 62% and 100%, respectively ( P < 0.001).…”
Section: Introductionmentioning
confidence: 87%
“…The subgroup analysis demonstrated that in addition to the ctDNA status, its dynamics should be considered, as the conversion of ctDNA from positive to negative from 4 to 12 wk after surgery might determine a more favorable prognosis (HR = 52.3, 95%CI: 7.2-380.5; P < 0.001)[ 37 ]. Polyanskaya et al [ 38 ] also confirmed the prognostic significance of ctDNA positivity after surgery in patients with stages I-III CRC. The 1-year PFS in the groups of positive and negative ctDNA status was 62% and 100%, respectively ( P < 0.001).…”
Section: Introductionmentioning
confidence: 87%